COUNSELING ON DEMENTIA, STRESS, AND STRESS REGULATION AMONG MALE PRISON INMATES IN PALU’S CITY - Fitriah Handayani; Jane Mariem Monepa; Muh Nur Ikhsan Liwang; Meillisa Silvana Petodo (LP2M STP Mataram, 2022)
Detention has become increasingly isolated since the Corona Virus Diseases 2019 (COVID-19) pandemic, as policies to prevent COVID-19 transmission have emerged. This may cause increased stress among inmates. Some research evidence links stress to poor health, memory loss, Alzheimer's, and dementia in general. Intrinsic and extrinsic stress factors are likely to persist as long as inmates are incarcerated (prison). Thus, stress, dementia, and stress regulation counseling and training are required.We educate inmates at the Palu male prison about dementia recognition, prevention, stress, and stress regulation.